P-005 Adoption of the transradial approach for cerebral angiography: learning curve and early experience. (23rd July 2017) - Sur, S; Snelling, B; Khandelwal, P; Caplan, J; Starke, R; Yavagal, D; Peterson, E
Abstract : Introduction: Transradial access (TRA) for endovascular procedures is associated with fewer complications and decreased recovery time compared to the traditional transfemoral approach. Further, in an aging population, anatomical conditions may frequently be better suited to a transradial approach for neurointerventional procedures, including cerebral angiography. While the feasibility and technical details of performing transradial cerebral angiography is well described, the learning curve for adopting a transradial approach to cerebral angiography has not been assessed. Here we report our early experience at a major academic, tertiary care center, in adopting a transradial approach to cerebral angiography and quantify the TRA learning curve for neurointerventional fellows previously trained in transfemoral angiography. Methods: Records of 115 consecutive TRA cerebral angiograms performed between January 2016 to February 2017 at Jackson Memorial Hospital in Miami, FL were reviewed. Learning curve was assessed by comparing efficiency (defined as minutes of fluoroscopy time divided by number of vessels catheterized for each angiogram) for each of the four operators between their initial and subsequent performance (Group 1 – angiograms #1–5; Group 2 – angiograms #11–15). Additionally, each fellow's experience was assessed longitudinally over the course of their training. Results: No major access site complications or permanent neurological injuries occurred. Selective vessel catheterization was performed frequently: the RICA was selected in 69.5% of cases (n=80), LICA in 48.7% (n=56), RVA in 71.3% (n=82), LVA in 23.4% (n=27), RECA in 24.3% (n=28) and LECA in 19.1% (n=22). Overall, a 31.6% improvement in procedural efficiency was observed between Group 1 (5.3 min/vessel) and Group 2 (3.6 min/vessel), consistent among all fellows (range 28.3%–35.4% improvement). Longitudinal efficiency plots for each fellow by number of angiograms performed, and days from initial exposure are shown in Figure 1 (Panel A and B, respectively), with accompanying exponential regression trendlines. Conclusions: Although there are several benefits to adopting a transradial technique for cerebral angiography, transitioning to this practice from the traditional transfemoral technique is associated with a learning curve. Nonetheless, technical efficiency can be improved significantly with relatively brief experience. Disclosures: S. Sur: None. B. Snelling: None. P. Khandelwal: None. J. Caplan: None. R. Starke: None. D. Yavagal: None. E. Peterson: None.